Structural differences between immature and mature articular cartilage of rabbits by microscopic MRI and polarized light microscopy. Issue 6 (3rd January 2022) - Mantebea, Hannah; Batool, Syeda; Singh, Amanveer; Hammami, Mohammed; Badar, Farid; Xia, Yang
Abstract: This study aimed to determine the structural features between immature and mature articular cartilage from the humeral and femoral joints of rabbits. Specimens of articular cartilage (n = 6 for immature tissue, n = 6 for mature tissue) that were still attached to the underlying bone from a humerus (shoulder joint) or femur (knee joint) were imaged using microscopic MRI (µMRI) and polarized light microscopy (PLM). Quantitative µMRI data with a pixel resolution of 11.7–13.2 µm revealed a number of differences between the immature and mature cartilage, including total thickness, and T2 and T1ρ relaxation values. Quantitative PLM data with a pixel resolution of 0.25–1 µm confirmed the µMRI results and revealed additional differences in cellular features between the tissues. The mature cartilage had a clearly defined tidemark, which was absent in the immature tissue. The ability to differentiate specific maturation‐related cartilage characteristics could be beneficial to translational studies of degenerative diseases such as osteoarthritis. Abstract : Mature articular cartilage is thinner with a more clearly defined tidemark than immature articular cartilage. Based on MRI, shorter T2 values in mature cartilage demonstrated a tighter interaction between water and macromolecules as compared to immature cartilage tissue. Humeral cartilage was found to have a more classical three‐zone fibril structure as compared to femoral cartilage.